Histone H3 binding to the PHD1 domain of histone demethylase KDM5A enables active site remodeling - James E. Longbotham; Cynthia M. Chio; Venkatasubramanian Dharmarajan; Michael J. Trnka; Idelisse Ortiz Torres; Devrishi Goswami; Karen Ruiz; Alma L. Burlingame; Patrick R. Griffin; Danica Galonić Fujimori (Nature Communications, 2019)
The demethylase activity of KDM5A is allosterically enhanced by binding of histone H3 to its PHD1 reader domain, through an unknown mechanism. Here the authors show that the PHD1 domain drives ligand-induced allosteric stimulation by stabilizing the binding of substrate to the catalytic domain.